1975
DOI: 10.1111/j.1365-2842.1975.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ability to recognize forms and oral motor ability in 11‐year‐old children*

Abstract: Oral ability to recognize forms and oral motor ability were examined in twenty children, aged 11 years, with normal occlusion. In the RF-test (recognition of form) the children identified the test pieces quicker but with a higher frequency of misidentification of the test pieces than a group of 17-year-old boys studied earlier. The effect of learning on the children was substantial with much quicker and greater certainty from one examination to another. Identification time and misidentification were positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…All but two of the children and all of the adults were able to comprehend and complete the task, indicating that this method can be used with pediatric as well as adult populations. That children took less time than adults to assess each letter is similar to previous reports that 11-year-old children took less time than did young adults (17-year-old boys) to identify shapes in an oral stereognosis task (Landt & Ingervall, 1975). In that study, although the children more frequently misidentified the shapes than did young adults, the absence of a positive correlation between assessment time and shape identification indicated that additional time spent assessing a stimulus did not aid the children in accurately determining its identity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All but two of the children and all of the adults were able to comprehend and complete the task, indicating that this method can be used with pediatric as well as adult populations. That children took less time than adults to assess each letter is similar to previous reports that 11-year-old children took less time than did young adults (17-year-old boys) to identify shapes in an oral stereognosis task (Landt & Ingervall, 1975). In that study, although the children more frequently misidentified the shapes than did young adults, the absence of a positive correlation between assessment time and shape identification indicated that additional time spent assessing a stimulus did not aid the children in accurately determining its identity.…”
Section: Discussionsupporting
confidence: 88%
“…The age-related difference in stimulus assessment time may be due to adults hesitating more than children when naming the letter; however, the shorter identification time among children did not affect task outcome. As in the Landt and Ingervall study (Landt & Ingervall, 1975), we found no relationship between stimulus identification time and overall lingual threshold in either adults or children, indicating that a longer time assessing each letter did not improve lingual acuity threshold.…”
Section: Discussionsupporting
confidence: 59%
“…For example, Landt and Ingervall (1975) suggest that an adult level of skill may not be reached by 11 years, while more speech-like aspects of development may reach their adult level around 14 years (Smith & Zelaznik, 2004). In contrast, other authors suggest that mature skill levels may be reached at a much younger age (Stark & Blackwell, 1997).…”
Section: Oral Motor Developmentmentioning
confidence: 99%
“…In accordance with the importance of OS, several studies using objective and quantifiable assessment tools to assess OS have been reported (7)(8)(9)15,16). However, most of these studies have focused on OS in elderly people.…”
Section: Discussionmentioning
confidence: 99%